Studi Pemanfaatan Ekstrak Rumput Laut Gracilaria verrucosa Sebagai Suplemen Pakan Untuk Meningkatkan Pertumbuhan Udang Putih (Litopenaeus vannamei) Dan Mengendalikan Populasi Bakteri Vibrio - Sasmaya, Eko; Subagiyo, Subagiyo; Ridlo, Ali (977-2407769)
The shrimp fishery has a high economic value. Data from the Ministry of Maritime Affairs and Fisheries (2011) states that the group of marine crustaceans in Indonesia has high potential with production reaching 381,288 tons / yr. From these results more than half of its cultivation. Aquaculture has the risk of which is the onset of the disease caused by viruses, fungi, bacteria, fungi and parasites that cause high levels of mortality and loss of quality of meat. One way to overcome these problems is to use feed supplementation. This study aimed to determine the effect of supplementation of extracts G. verrucosa on feed on shrimp growth (weight and length), specific growth rate, survival rate of shrimp, feed conversion ratio, and Vibrio bacterial populations. The research was conducted through laboratory experimental method to the study design completely randomized design (CRD) with 3 treatments and each treatment with three replications. The treatments tested were feed by supplementing 0.5%, 1% and 2% respectively supplementation performed 3 times repetition. Feed obtained by extraction G. verrucosa, that is by G. verrucosa put in a pot submerged Stainless steel up to boiling and boil for Â± 2 hours and obtained extracts G. verrucosa, then performed using a rotary solvent evaporation process to obtain dry extracts G. verrucosa. Further supplementing the feed. Results showed that the extract of G. verrucosa able to improve and control the growth of white shrimp vibrio bacteria populations in the intestines white shrimp (L. vannamei). In this study the condition of seaweed extract supplementation G. verrucosa at a concentration of 2% were able to increase the weight of shrimp growth of 131.43% and a growth of 32.50% shrimp length than controls during 28 days of treatment, as well as being able to control populations of bacteria vibrio, vibrio that reduces the total amount of 78.18% compared to controls at the third week.